Effectiveness of Local Wisdom-Based Independent Curriculum Teaching Modules in Improving Learning Outcomes Indonesia - ., Salmia; ., Nursalam; Bancong , Hartono (Journal of Ecohumanism, 2024)
The efficacy of independent curriculum teaching modules based on local wisdom in enhancing learning outcomes in Indonesia. The research method employed is an experiment with a randomized control group design. The sample consists of randomly selected schools in specific areas, with one group receiving instruction using the local wisdom-based Independent Curriculum teaching modules and another group serving as a control that continues to use the conventional curriculum—the efficacy of independent curriculum teaching modules based on local wisdom in enhancing learning outcomes in Indonesia. The results indicate that students who learned using the Independent Curriculum teaching modules significantly improved their understanding and academic achievement. The relevance and efficacy of learning can be increased by incorporating local wisdom into the classroom, as these data demonstrate. Future studies could involve long-term monitoring of their impact on students' learning outcomes over time, as well as factors influencing the success of implementation.